2011
DOI: 10.1186/2045-8118-8-21
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-beta transporter expression at the blood-CSF barrier is age-dependent

Abstract: BackgroundAge is the major risk factor for many neurodegenerative diseases, including Alzheimer's disease (AD). There is an accumulation of amyloid-beta peptides (Aβ) in both the AD brain and the normal aging brain. Clearance of Aβ from the brain occurs via active transport at the blood-brain barrier (BBB) and blood-cerebrospinal fluid barrier (BCSFB). With increasing age, the expression of the Aβ efflux transporters is decreased and the Aβ influx transporter expression is increased at the BBB, adding to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(105 citation statements)
references
References 57 publications
2
102
0
1
Order By: Relevance
“…At the ependyma and pia, molecules such as HVA and 5-HIAA diffuse out of ECSB into CSF for removal by carriermediated transport and bulk flow.In Alzheimer"s disease, the concentration of A 42 in CSF is on average lower than in normal age-matched controls. Active carrier-mediated transport processes that remove A from CSF (Pascale et al, 2011) do not resemble the passive lymph circulation.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…At the ependyma and pia, molecules such as HVA and 5-HIAA diffuse out of ECSB into CSF for removal by carriermediated transport and bulk flow.In Alzheimer"s disease, the concentration of A 42 in CSF is on average lower than in normal age-matched controls. Active carrier-mediated transport processes that remove A from CSF (Pascale et al, 2011) do not resemble the passive lymph circulation.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Similarly, the bidirectional transporter LRP-2 and influx transporter RAGE were decreased and unchanged with age, respectively. 139 These changes were associated with decreased concentrations of Ab42 in the CP, suggesting that the BCSFB compensates for agedependent transporter dysfunctions in the BBB. 139 In humans with AD, increased Ab deposition in the CP is observed.…”
Section: Blood-cerebrospinal Fluid Barrier Transport In Aging Andmentioning
confidence: 99%
“…139 These changes were associated with decreased concentrations of Ab42 in the CP, suggesting that the BCSFB compensates for agedependent transporter dysfunctions in the BBB. 139 In humans with AD, increased Ab deposition in the CP is observed. 140 Furthermore, Ab deposition in CP epithelial cells causes oxidative damage, disruption of the BCSFB, and cell death.…”
mentioning
confidence: 99%
“…Recent research into sporadic Alzheimer's disease (AD) has confirmed that aging is the single most important risk factor for AD genesis, and that the accumulation of amyloid-beta (Ab) peptides as insoluble plaques and soluble oligomeric and intermediate forms are responsible for oxidative damage to neurons, eventually leading to neuronal death (Querfurth and LaFerla, 2010). More importantly, it has been shown that the accumulation of amyloid is not due to increased production, but rather to decreased clearance of Ab from the brain (Mawuenyega et al, 2010).…”
Section: Introductionmentioning
confidence: 98%